2018
DOI: 10.1002/er.4185
|View full text |Cite
|
Sign up to set email alerts
|

Parametric analysis on the performance of an experimental ammonia/lithium nitrate absorption cooling system

Abstract: Summary The present study reports the experimental results of a new absorption cooling system utilizing stainless steel plate heat exchangers in all the main components. The system operated with the ammonia‐lithium nitrate working pair. Several parametric analyses were performed in order to investigate the effect of the generation and condensation temperatures, solution mass flow rate, solution volume and expansion valve aperture on the cooling power, evaporation temperatures, and coefficient of performance (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Several studies have investigated and analyzed compact heat exchangers as a way to reduce the amount of working fluid, as well as reducing the global size of the system, and therefore costs, by the use of compact components in absorption refrigeration systems to use low-temperature sources for the activation [26,85]. Additionally, due to the increasing performance of the refrigeration systems and reduction in energy consumption, new configurations are possible, such as adding multiple absorbers [77], compact heat exchanger components [26,27,76,88] or including ejectors of the systems [84], or combining sorption and mechanical compression systems [80,89], or integrating different systems to use polygeneration plants [67,90].…”
Section: Theoretical and Numerical Assessment On Absorption Chillermentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have investigated and analyzed compact heat exchangers as a way to reduce the amount of working fluid, as well as reducing the global size of the system, and therefore costs, by the use of compact components in absorption refrigeration systems to use low-temperature sources for the activation [26,85]. Additionally, due to the increasing performance of the refrigeration systems and reduction in energy consumption, new configurations are possible, such as adding multiple absorbers [77], compact heat exchanger components [26,27,76,88] or including ejectors of the systems [84], or combining sorption and mechanical compression systems [80,89], or integrating different systems to use polygeneration plants [67,90].…”
Section: Theoretical and Numerical Assessment On Absorption Chillermentioning
confidence: 99%
“…Tables 7 and 8 summarize the studies about absorption chillers using either experimental analysis or numerical and theoretical studies. Analysis of influences on the coefficient of heat transfer of the ARS New correlation was proposed to predict the impact of the settings on the boiling heat transfer coefficient Jiménez-Garcia and Rivera [76] Assessment of the use of plate heat exchanger on an absorption chiller The cooling power of 3 kW was reached with 6 • C of chilled water temperature and COP of 0.62…”
Section: Miscellaneous Assessment On Absorption Chillermentioning
confidence: 99%
See 2 more Smart Citations
“…By the second‐law analysis, Farshi et al have concluded that the NH 3 ‐NaSCN chiller operates on a narrow range of generator temperatures. Jiménez‐García and Rivera have parametrically analyzed the NH 3 ‐LiNO 3 system and experimentally attained 3.1 kW of cooling at 6°C evaporator temperature with a COP of approximately 0.62. Pandya et al have observed that optimized system COPs (SCOPs) for the NH 3 ‐LiNO 3 pair are 11.07%, 6.06%, 9.77%, and 6.96% higher compared with those for the NH 3 ‐NaSCN pair for a flat‐plate collector (FPC), an evacuated‐tube collector, a compound‐parabolic collector, and a parabolic‐trough collector (PTC) coupled with a VARS, respectively.…”
Section: Introductionmentioning
confidence: 99%